Characteristics of Composite Flour (Biang fish Ilisha elongata and Sago) For the Development of Good Nutritional Food Products. Issue 1 (November 2021) - Sumarto, S; Desmelati, D; Karnila, R; Dahlia, D; Suparmi, S; Hasan, B
Abstract: Composite flour is a mixture of fish flour and sago flour to increase nutrition in food products. This study aims to increase the nutritional value of food products with sago flour as raw material. Composite flour from fish and sago flour were 0%, 2%, 4%, 6%, 8%, and 10% Biang fish to the amount of sago flour. The results of the research on fish flour Ilisha elongata showed a yellowish-white color with a whiteness degree of 75.8%. Fish flour has a yield of 28.9% with a fineness level on a 100-mesh sieve. The results show the characteristics of the composite flour of Biang fish and sago, respectively, the color of the flour was white-gray to cream color; having nutritional characteristics, respectively, the moisture content is 9.62%; 9.57%; 9.55%; 9.42%; 9.26%, and 9.20%. The protein content was 0.25%; 3.58%; 4.09%; 4.99%; 5.98%, and 6.39%. The fat content was 0.41%, 0.24%, 0.29%; 0.37%; 0.40%; 0.42%. The ash contained 0.27%, 0.34%, 0.50%, 0.57%, 0.69%, and 0.76%. The carbohydrates were 89.45%; 86.27%; 85.57%; 84.65%; 83.67%, and 83.23%. The calcium content was 1130 mg/kg; 1901 mg/kg; 2687 mg/kg; 2770 mg/kg; 2827 mg/kg and 2869 mg/kg. The addition of fish flour can increase the nutritional value of composite flour made from sago flour and has the potential to develop nutritious food products.